Damage monitoring of adhesively bonded composite-metal hybrid joints using carbon nanotube-based sensing layer. Issue 1 (2nd January 2020) - Doshi, Sagar M.; Lyness, Tyler B.; Thostenson, Erik T.
Abstract: Improving mechanical properties and decreasing costs have significantly increased the use of fiber composites in automotive, aerospace, and civil engineering applications. Structural composites are bonded to traditional metallic materials in a variety of applications, and mechanical fasteners often cannot be used due to the low bearing strength of composites. With the increasing use of adhesives in load-bearing structures, novel techniques are required for monitoring the structural integrity of adhesive joints. Previously, carbon nanotubes (CNTs) have been added to adhesives and resins to create in-situ sensors, but the increased viscosity and potential for galvanic corrosion remains a challenge. In this research, a piezoresistive carbon nanotube-based sensing layer is embedded in a composite/steel adhesive joint for damage sensing. The use of a thin sensing layer with low-fiber volume fraction enables the use of existing adhesives without causing any major changes in the physical properties of the adhesives or the curing cycle and reduces the chances of galvanic corrosion. Different approaches of using an adhesive layer and a nonconductive fabric are investigated for insulation of the sensing layer. The nonconductive fabric approach for insulating the specimen yields better mechanical properties as the there are no weak interfaces in the adhesive bondline. Additionally, it is more convenient for scaling up for field applications as the adhesive is cured in one stage. The sensing layer can not only be used to detect incipient damage in the joint, but also identify different modes of failure. Graphical Abstract: